2012
DOI: 10.1111/j.1750-3841.2012.02910.x
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Fruit Moisture Content Heralds and Might Launch the Onset of Ripening Processes

Abstract: This study suggests that decline in fruit water content is an early event in fruit ripening. This information may be used to gauge fruit maturity for appropriate harvest date and for processing. Control of fruit hydration state might be used to regulate the onset of fruit ripening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 117 publications
2
20
0
Order By: Relevance
“…Changes in the bound water content caused by different environmental factors have been observed in distinct plants (Yoshida et al 1997;Gusta et al 2004) and in different tissues of harvested table grape clusters (Goñi et al 2011). In view of these results, it is reasonable to ask if the changes in water status could be a signal that these concentrations of CO 2 induce metabolic responses in fruit during storage, in line with that suggested by Passioura and Munns (2000) for leaves or for the onset of ripening in fruit suggested by Frenkel and Hartman (2012).…”
Section: Water Statussupporting
confidence: 50%
See 1 more Smart Citation
“…Changes in the bound water content caused by different environmental factors have been observed in distinct plants (Yoshida et al 1997;Gusta et al 2004) and in different tissues of harvested table grape clusters (Goñi et al 2011). In view of these results, it is reasonable to ask if the changes in water status could be a signal that these concentrations of CO 2 induce metabolic responses in fruit during storage, in line with that suggested by Passioura and Munns (2000) for leaves or for the onset of ripening in fruit suggested by Frenkel and Hartman (2012).…”
Section: Water Statussupporting
confidence: 50%
“…The fact that only about 10 % of the solid matter in strawberries has to cope with a larger amount of liquid could explain, in part, their high perishability and susceptibility to textural damage, fungal decay, and liquid leakage. Moreover, changes in fruit water status regulate ripening processes to some extent (Frenkel and Hartman 2012) and modifications in the content of the different water fractions have been reported (Goñi et al 2007). Changes in the bound water fraction are at least partially the result of modifications in the levels of hydrophilic molecules with high water-binding capacity.…”
Section: Introductionmentioning
confidence: 99%
“…One such field is in plant science, dealing with water relations. Another field is the post harvest biology, where one has found that cell wall hydration and swelling are higly relevant processes for of fruit ripening [26,87]. Its significance is even larger under drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…92% and 0.3%, respectively. According to Frankel and Hartman (2012) contents of water in strawberry and tomato prior to their harvesting (green fruit) changed only by 0.02% by the time the fruit turned red. Statistically significant changes were observed in the value of total solids in Bonaparte variety of tomatoes.…”
Section: Resultsmentioning
confidence: 99%